2018
DOI: 10.1186/s40345-018-0135-7
|View full text |Cite
|
Sign up to set email alerts
|

Lithium during pregnancy and after delivery: a review

Abstract: Lithium is an effective treatment in pregnancy and postpartum for the prevention of relapse in bipolar disorder. However, lithium has also been associated with risks during pregnancy for both the mother and the unborn child. Recent large studies have confirmed the association between first trimester lithium exposure and an increased risk of congenital malformations. Importantly, the risk estimates from these studies are lower than previously reported. Tapering of lithium during the first trimester could be con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(92 citation statements)
references
References 92 publications
1
88
0
3
Order By: Relevance
“…A case report reported that a 31-year-old Caucasian woman with bipolar disorder type I manifested a cutaneous adverse reaction after treated with Li 2 CO 3 (Pinna et al, 2017). Some clinical cohort studies also indicated the association between lithium treatment and congenital malformation, raising the concern about the possible teratogenicity of lithium exposure during the first trimester (Poels et al, 2018).…”
Section: Challenge For the Use Of Lithiummentioning
confidence: 99%
“…A case report reported that a 31-year-old Caucasian woman with bipolar disorder type I manifested a cutaneous adverse reaction after treated with Li 2 CO 3 (Pinna et al, 2017). Some clinical cohort studies also indicated the association between lithium treatment and congenital malformation, raising the concern about the possible teratogenicity of lithium exposure during the first trimester (Poels et al, 2018).…”
Section: Challenge For the Use Of Lithiummentioning
confidence: 99%
“…The amounts of lithium used to calibrate LiDCOplus are very low, especially when compared with standard therapeutic doses in pregnant women with bipolar disorders; however, lithium can cross the placenta freely. Two recent meta‐analyses addressed the long‐term neurodevelopment outcomes in offspring with in‐utero exposure to lithium. While preclinical data in animals suggest a potential adverse effect, clinical data in humans, although limited to 97 children, seem reassuring.…”
Section: Methods Of Co Measurementmentioning
confidence: 99%
“…It has been suggested that an increase in the prevalence of Ebstein’s anomaly may be associated with maternal mental illness itself rather than lithium exposure 17. Later in the pregnancy lithium use may be associated with polyhydramnios due to fetal polyuria, third trimester ultrasound scanning should be considered 18…”
Section: Is Her Current Medication Suitable For Pregnancy? Are the Mementioning
confidence: 99%